Monopolizing Force? Police Legitimacy and Public Attitudes Toward the Acceptability of Violence - Jackson, J; Huq, A; Bradford, B; Tyler, T (2013)
Why do people believe that violence is acceptable? In this article, the authors study people's normative beliefs about the acceptability of violence to achieve social control (as a substitute for the police, for self-protection and the resolution of disputes) and social change (through violent protests and acts to achieve political goals). Addressing attitudes toward violence among young men from various ethnic minority communities in London, the authors find that procedural justice is strongly correlated with police legitimacy, and that positive judgments about police legitimacy are associated with more negative views about the use of violence. They conclude with the idea that police legitimacy has an additional, hitherto unrecognized, empirical property-by constituting the belief that the police monopolise rightful force in society, legitimacy has a "crowding out" effect on positive views of private violence. © 2013 American Psychological Association.